Faktor Gaya Hidup Hedonis dan Persepsi Kemudahan Penggunaan Terhadap Keputusan Generasi Z Menggunakan Spaylater di Surabaya - Andi Thirah Koesitiany Mallarangan; Rizky Dermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The rapid development of the internet has encouraged Generation Z to adopt a hedonistic lifestyle, supported by the convenience offered by online loan services like SPayLater. This study aims to identify the influence of a hedonistic lifestyle and perceived ease of use on the decision to use SpayLater among Generation Z in Surabaya. This quantitative research sampled 96. The sampling technique used was accidental sampling, targeting respondents who belong to Generation Z, are aware of SPayLater, and reside in Surabaya. The analysis technique applied in this study is Partial Least Squares (PLS) using SmartPLS 4, including validity tests, reliability tests, and hypothesis testing. The results showed that the variables of hedonistic lifestyle and perceived ease of use have a positive and significant influence on the decision to use SpayLater.